Ultra-Highly Stiff and Tough Shape Memory Polyurea with Unprecedented Energy Density by Precise Slight Cross-Linking - Chen, Jiaoyang (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.